Trust her - Berry, Flynn, 1986- (Viking, 2024)
"Three years after they narrowly escaped the IRA's worst punishment for informing, Northern Irish sisters Tessa and Marian Daly have built a new life in Dublin with their young children. Though Tessa is haunted by the abrupt and violent end to her old life, she does her best to immerse herself in the joys of Finn's childhood and the rhythms of her new job at the Irish Times. It's a small island, though, and just as quickly as they disappeared, figures from the sisters' past surface to reentrench them in the conflict. Tessa is told she must track down her old handler from MI5, Eamonn, and attempt to turn him into an IRA informant, or lose everything. Tessa's reunion with Eamonn revives a host of feelings she has long attempted to bury. As their relationship intensifies and pressure from the local authorities and the IRA mounts, long-held secrets bubble to the surface, and Tessa must navigate a treacherous landscape of shifting loyalties, all while trying to protect the child she holds most dear."--